Impact of Anticoagulation on Mortality and Resource Utilization Among Critically Ill Patients With Major Bleeding. Issue 4 (April 2020) - Fernando, Shannon M.; Mok, Garrick; Castellucci, Lana A.; Dowlatshahi, Dar; Rochwerg, Bram; McIsaac, Daniel I.; Carrier, Marc; Wells, Philip S.; Bagshaw, Sean M.; Fergusson, Dean A.; Tanuseputro, Peter; Kyeremanteng, Kwadwo
Abstract : Objectives: Patients with major bleeding are commonly admitted to the ICU. A growing number are on either oral or parenteral anticoagulation, but the impact of anticoagulation on patient outcomes is unknown. We sought to examine this association between anticoagulation therapy and mortality, as well as the independent effects of warfarin compared to direct oral anticoagulants. Design: Analysis of a prospectively collected registry (2011–2017) of consecutive ICU patients admitted with major bleeding (as defined by International Society on Thrombosis and Haemostasis clinical criteria). Setting: Two hospitals within a single tertiary care level hospital system. Patients: We analyzed 1, 598 patients identified with major bleeding, of which 245 (15.3%) had been using anticoagulation at the time of ICU admission. Of patients on anticoagulation, 149 were using warfarin, and 60 were using a direct oral anticoagulant. Interventions: None. Measurements and Main Results: The primary outcome, in-hospital mortality, was analyzed using a multivariable logistic regression model. Patients with anticoagulation-associated major bleeding had higher in-hospital mortality (adjusted odds ratio, 1.49; 95% CI, 1.16–1.92). Among survivors, anticoagulation use was associated with longer median hospital length of stay, and higher mean costs. No differences in hospital mortality were seen between warfarin- and direct oral anticoagulant-associated major bleeding. Patients with warfarin-associated major bleeding had longer median length of stay (11 vs 6 d; p = 0.02), and higher total costs than patients with direct oral anticoagulant-associated major bleeding. Conclusions: Among ICU patients admitted with major bleeding, pre-admission anticoagulation use was associated with increased hospital mortality, prolonged length of stay, and higher costs among survivors. As compared to direct oral anticoagulants, patients with warfarin-associated major bleeding had increased length of stay and costs. These findings have important implications in the care of ICU patients with major bleeding. Abstract : Supplemental Digital Content is available in the text.